Alternative carbon price trajectories can avoid excessive carbon removal - Jessica Strefler (Nature Portfolio, 2021)
Many trajectories for reaching climate change mitigation targets exaggerate the long-term need for CO2 removal (CDR) because they assume an exponentially increasing carbon price. Here the authors analyse alternative carbon price pathways that halt warming while limiting CDR, and may be easier to implement.